PENYELESAIAN SENGKETA CICILAN EMAS ATAS KETIDAKMAMPUAN PEMBAYARAN ANGSURAN NASABAH PADA PEGADAIAN SYARIAH CABANG PAMEKASAN - Hidayatullah, Hidayatullah; Eri Hariyanto, Eri Hariyanto; Rudy Haryanto, Rudy Haryanto; Hidayat, Hidayat (JSE: Jurnal Sharia Economica, 2026)
The problem that arises in the settlement of gold installment disputes is due to the increasing number of customers who default on payments as a result of unstable economic conditions, thereby creating the potential for disputes between the institution and its customers. This study aims to analyze the mechanism for resolving gold installment disputes due to customers' inability to pay installments at the Pamekasan Branch of Pegadaian Syariah and to examine its conformity with the principles of Islamic economic law. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, direct observation, and documentation of the pawnshop and customers involved in gold installment financing cases. The results show that dispute resolution at the Pamekasan Branch of Pegadaian Syariah is carried out through deliberation and financing restructuring, rather than through litigation. This conflict resolution is implemented in three phases: (1) a deliberative approach based on ishlah, (2) reconfiguration of the financing scheme, and (3) arbitration through BASYARNAS. Empirical evidence shows that 83% of total cases were successfully resolved through deliberative mechanisms without involving formal litigation processes. The consumer satisfaction index reached 78%, indicating the effectiveness of a resolution strategy that prioritizes humanistic dimensions based on sharia values. This study recommends two main strategies: first, intensifying sharia financial literacy education programs; second, establishing a special consultative unit that functions as a preventive instrument against potential ongoing conflicts in the future.